2022
DOI: 10.1039/d2qi01079h
|View full text |Cite|
|
Sign up to set email alerts
|

A photoactive lysosome targeting RuII complex downregulates stemness genes in oral squamous cell carcinoma

Abstract: Half-sandwich Ru-arene complexes with curcuminoids exhibit excellent chemotherapeutic effects but their photoactivity remains unexplored. Here we present a 1,3-diketone coordinated RuII-arene complex (1) as a type-I photosensitizer (PS) displaying efficacy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…It has been established that the metal complexation of curcumin increases its stability and bioavailability. Moreover, curcumin is reported as a good photosensitizer due to its efficient singlet oxygen generation ability under visible light . Therefore, in recent years, several curcumin-based metal complexes have been reported for PDT. , Several curcumin complexes of V­(IV), Fe­(III), Co­(II), Co­(III), Pt­(II), Ru­(II), Ir­(III), Os­(II), Rh­(III), etc. are explored as photosensitizers for PDT application, but the example of Zn­(II)-curcumin complexes in PDT is very rare. , To the best of our knowledge, Chakraborty et al reported the only Zn­(II)-curcumin complex with BODIPY as a pendant for PDT activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that the metal complexation of curcumin increases its stability and bioavailability. Moreover, curcumin is reported as a good photosensitizer due to its efficient singlet oxygen generation ability under visible light . Therefore, in recent years, several curcumin-based metal complexes have been reported for PDT. , Several curcumin complexes of V­(IV), Fe­(III), Co­(II), Co­(III), Pt­(II), Ru­(II), Ir­(III), Os­(II), Rh­(III), etc. are explored as photosensitizers for PDT application, but the example of Zn­(II)-curcumin complexes in PDT is very rare. , To the best of our knowledge, Chakraborty et al reported the only Zn­(II)-curcumin complex with BODIPY as a pendant for PDT activity .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, several curcumin-based metal complexes have been reported for PDT. , Several curcumin complexes of V­(IV), Fe­(III), Co­(II), Co­(III), Pt­(II), Ru­(II), Ir­(III), Os­(II), Rh­(III), etc. are explored as photosensitizers for PDT application, but the example of Zn­(II)-curcumin complexes in PDT is very rare. , To the best of our knowledge, Chakraborty et al reported the only Zn­(II)-curcumin complex with BODIPY as a pendant for PDT activity . Thus, although curcumin-based Zn­(II) complexes have been well-explored as cancer chemotherapeutics, their use as photosensitizers for PDT has not been well-explored.…”
Section: Introductionmentioning
confidence: 99%
“…58−60 CSCs exhibit deregulation of Notch, Wnt, or Hedgehog pathways; 61 hence, inhibiting these pathways presents a viable option to kill CSCs. 51,62,63 Our investigation monitored the Notch pathway and the common checkpoints of stemness via the three pathways (Figure 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The investigation was carried out against oral squamous cell carcinoma (OSCC) since it has a major occurrence in the Southeast Asian subcontinent, yet development of new drugs for OSCC is scarce. Potential involvement of CSCs in oral tumor initiation and progression shows a 5-year survival rate of around 50% . The low survival rate is due to recurrence as a result of heterogeneity among cancer cells including CSCs. CSCs exhibit deregulation of Notch, Wnt, or Hedgehog pathways; hence, inhibiting these pathways presents a viable option to kill CSCs. ,, Our investigation monitored the Notch pathway and the common checkpoints of stemness via the three pathways (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation